Effects of Constructive Controversy and Self-Efficacy on Students’ Attitude to Genetics' Concepts - Ojo, Ayodeji Temitope (PEDAGOGIA, 2024)
Genetics concepts (GCs) play a vital role in human development and societal well-being. Despite their importance, advancements in genetics have sparked public controversies, particularly in areas such as genetic modification of organisms and sex determination. Reports indicate that students often exhibit negative attitudes toward GCs, while previous teaching interventions have failed to effectively integrate socioscientific issues. This study aimed to enhance students' attitudes toward GCs by employing the Constructive Controversy Strategy (CCS), grounded in situated learning theory. A pretest-posttest control group quasi-experimental design was adopted, involving secondary school science students from six public schools. Participants were randomly assigned to either the CCS group (121 students) or the conventional strategy group (119 students). Data were analyzed using analysis of covariance (ANCOVA) at p 0.05. The results revealed a significant main effect of treatment on students' attitudes toward GCs (F(1,215) = 4.42, partial η² = 0.02). Genetics self-efficacy also showed a significant main effect (F(2,214) = 3.12, partial η² = 0.03), and a significant interaction effect was observed between treatment and genetics self-efficacy (F(2,213) = 3.04, partial η² = 0.05). These findings demonstrate that CCS is effective in improving students' attitudes toward GCs, underscoring the importance of integrating socioscientific issues into genetics education.